Uncultivated Microorganisms - Epstein, Slava S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The number of existing microbial species may be in the millions, but only a few thousand have been isolated in pure culture and described. The principal reason for this tremendous disparity is that, mysteriously, over 99% of all environmental microorganisms refuse to grow in the laboratory. The phenomenon of microbial uncultivability has been recognized as one of the main challenges for basic and applied microbiology, and finding a way to access this uncultivated microbial majority may change many aspects of biology and biotechnology as we know them today. This volume describes the discovery of the phenomenon, the current hypotheses on its physiological and molecular nature, state-of-the-art approaches to "outsmarting" the uncultivated microorganisms, and the importance of the uncultivated microbial majority in medicine and biotechnology. It reveals the hidden universe of uncultivated microorganisms, their unparalleled diversity and enormous potential for application.
Viable but Not Cultivable Bacteria -- General Model of Microbial Uncultivability -- Statistical Estimation of Uncultivated Microbial Diversity -- Detection and Characterization of Uncultivated Microorganisms Using Microarrays -- Persisters, Biofilms, and the Problem of Cultivability -- Metagenomics and Antibiotic Discovery from Uncultivated Bacteria -- Taking the Concept to the Limit: Uncultivable Bacteria and Astrobiology -- Single Cell Whole Genome Amplification of Uncultivated Organisms -- Physiological and Ecological Adaptations of Slow-Growing, Heterotrophic Microbes and Consequences for Cultivation -- Characterizing Microbial Population Structures through Massively Parallel Sequencing -- The Seabed as Natural Laboratory: Lessons From Uncultivated Methanotrophs.
Keywords: Medicine; Human physiology; Molecular biology; Microbiology; Microbial ecology; Molecular ecology; Microbial genetics; Microbial genomics; Biomedicine; Human Physiology; Microbial Ecology; Microbial Genetics and Genomics; Molecular Ecology; Applied Microbiology; Molecular Medicine; Electronic books